2014
DOI: 10.1164/rccm.201403-0446oc
|View full text |Cite
|
Sign up to set email alerts
|

Bosentan in Pulmonary Hypertension Associated with Fibrotic Idiopathic Interstitial Pneumonia

Abstract: Rationale: Pulmonary hypertension (PH) associated with fibrotic idiopathic interstitial pneumonia (IIP; idiopathic pulmonary fibrosis and nonspecific interstitial pneumonia) confers important additional morbidity and mortality.Objectives: To evaluate the safety and clinical efficacy of the dual endothelin-1 receptor antagonist bosentan in this patient group.Methods: In a randomized, double-blind, placebo-controlled study, 60 patients with fibrotic IIP and right heart catheter confirmed PH were randomized 2:1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
163
1
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 193 publications
(183 citation statements)
references
References 33 publications
3
163
1
16
Order By: Relevance
“…The development of PH in ILD is a strong predictor of poor survival [46,56,57]. Unfortunately, the use of anti-PH treatments in this group of patients has not generated much optimism to date, as outlined in the previous sections and by a recent placebo-controlled trial of bosentan in patients with idiopathic interstitial pneumonias and PH [58]. The mechanisms thought to contribute to PH in ILD vary, and include hypoxic vasoconstriction, vascular remodelling, vessel ablation, vascular occlusion and compression.…”
Section: Nocturnal Hypoxia and Supplemental Oxygen In Ipfmentioning
confidence: 99%
“…The development of PH in ILD is a strong predictor of poor survival [46,56,57]. Unfortunately, the use of anti-PH treatments in this group of patients has not generated much optimism to date, as outlined in the previous sections and by a recent placebo-controlled trial of bosentan in patients with idiopathic interstitial pneumonias and PH [58]. The mechanisms thought to contribute to PH in ILD vary, and include hypoxic vasoconstriction, vascular remodelling, vessel ablation, vascular occlusion and compression.…”
Section: Nocturnal Hypoxia and Supplemental Oxygen In Ipfmentioning
confidence: 99%
“…The primary outcome was the fall of pulmonary vascular resistance by 20% or more over 16 weeks. The study was negative [61].…”
Section: Treatment Considerations Of Ph In the Course Of Dpldsmentioning
confidence: 90%
“…Corte et al didn't observe any significant difference in the oxygen saturation and oxygen requirement between bosentan and placebo groups in the patients with IPF and fibrotic NSIP [61]. Zisman et al found improved oxygenation in the group of IPF patients treated with Sildenafil in the STEP-IPF study [57].…”
Section: Treatment Considerations Of Ph In the Course Of Dpldsmentioning
confidence: 99%
“…An earlier report from the same study showed that treatment with ambrisentan is not effective in these patients and is even associated with shorter time to disease progression [34]. In a later placebo-controlled trial by CORTE et al [35], patients with IPF and pulmonary hypertension were randomised to bosentan or placebo. At a 16-week follow-up, no difference was found between the placebo and treatment group in pulmonary haemodynamics, symptoms and functional capacity in patients with idiopathic interstitial pneumonia and pulmonary hypertension.…”
Section: Pulmonary Hypertension Secondary To Pulmonary Diseasementioning
confidence: 99%